The role played by Netherlands Development Organization in promoting poverty alleviation for smallholder farmers in Domboshava using the Market- Based Approach (The SNV Case 2012-2014). - Ziyambi, Tsitsi T. (Midlands State University, 2017)
This research investigated the effectiveness of market based approach in promoting poverty alleviation from smallholder farmers in Zimbabwe. The research gathered evidence from a group of smallholder farmers in Domboshava, Zimbabwe, who are part of a market- based approach project run by SNV in order to sustain and improve the livelihoods of vulnerable and emerging rural farming households in Domboshava and thus reduce their dependence on humanitarian assistance. Literature review was conducted so as to assess what other scholars say about the market- based approach. Data was collected through Focus Groups Discussions, key informant interviews and questionnaires. The focus group discussion comprised of ten smallholder farmers who are in the leadership of the association. The key informant interviews were conducted with the chairperson of the group and the project manager from SNV. Forty questionnaires were administered with the smallholder farmers. Key findings were that the market- based approach being implemented by SNV has led to increased incomes, food security and employment for the smallholder farmers. The data was compared with the points raised in the literature review. The comparison showed that most of the key positive impacts of the market- based approach raised in Domboshava case study were similar to those identified in the literature review. The study came to the conclusion that if a market- based approach is implemented in all provinces in Zimbabwe the poverty rates will decrease.